Guyana Lands and Surveys Commission - (:unkn) unknown (My University, 2011)
OBJECTIVES * to have general administrative control of the Commission and report to the Board on a monthly basis. * to prepare land use plans for Guyana or any part of Guyana, except any municipality which is subject to a planning scheme (or interim development control pending the preparation of a planning scheme) under the Town and Country Planning Act; * to establish and maintain liaison with the responsible agencies to promote and monitor the use public lands, the maintenance of drainage and irrigation system, access roads and other infrastructure, through such measures as may be appropriate; * to compile and maintain an inventory of all the land resources of Guyana, their quality, degree, pattern of utilization and related matters * to advise the Government on policy relating to public land surveys; land surveys and any other matters related to the functions of Commission; * to initiate studies into and formulate policy on the development of public lands, including the feasibility of specific land development projects;
Keywords: Land